Implementation Of Network Packet Filtering With Extended Acl Methods On Microtik In Securing Internet Connection Office AFD IV Butong Sulfur Unit - Gery Chandra Purba (INFOKUM, 2021)
The need for information and internet access is currently very high. To fulfill that, one way is to use computer networks as the medium. In a network that already uses a Virtual Local Area Network (VLAN), it still requires the application of Network Packet Filtering with the Access Control List (ACL) method to regulate the access rights of each device on the network. Access Control List (ACL) can filter data traffic of a network by filtering whether the packets are fit to pass or be stopped. The network is built using several different network devices, one of which is a router. A router is a device that can process data packets that differ between networks (between networks) through a process called routing. Lots of companies produce routers, Mikrotik is one company that produces routers. Mikrotik is easy to operate because it can be helped using additional software, namely Winbox in the GUI display, besides that there is a hotspot server inside which consists of several network management facilities that we can set according to network needs